Susceptibility of the Japanese beetle, Popillia japonica (Newman) (Coleoptera: Scarabaeidae), to entomopathogenic Hypocreales fungi - Giroux, François; Lavallée, Robert; Bauce, Éric; Guertin, Claude (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2015)
The susceptibility of adults and larvae of the Japanese beetle to isolates of the fungi Beauveria bassiana, B. brongniartii, Metarhizium anisopliae, Lecanicillium longisporum and L. muscarium (Ascomycota: Hypocreales) was evaluated in laboratory bioassays. The presence of intra- and interspecific variations regarding the pathogenicity of the isolates was investigated. Results show that most of the fungal isolates caused mortality in adults and larvae. Isolates M. anisopliae INRS 705 and B. bassiana INRS 236 induced 70.3% and 65.2% of mortality in P. japonica adults, respectively, and both caused the death of about 37% of larvae. Of the 17 tested isolates, 13 caused larval mortality. However, no significant difference was found between the susceptibility of larvae to isolates from different species and those from a same species. Lecanicillium species are undoubtedly not pathogenic to adults and seem to have few effects on larvae. Based on the results obtained with the selected isolates, intra- and interspecific differences relative to the pathogenicity of the isolates appeared to be present. Overall, this study expanded the knowledge about P. japonica susceptibility towards entomopathogenic Hypocreales fungi. The implications of this study regarding the development of a biological control agent are discussed.